2021
DOI: 10.1039/d1sm01052b
|View full text |Cite
|
Sign up to set email alerts
|

Non-hyperuniform metastable states around a disordered hyperuniform state of densely packed spheres: stochastic density functional theory at strong coupling

Abstract: Disordered and hyperuniform structures of densely packed spheres near and at jamming are characterized by vanishing of long-wavelength density fluctuations, or equivalently by long-range power-law decay of the direct correlation...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 106 publications
(525 reference statements)
0
12
0
Order By: Relevance
“…It has been shown that the constrained free energy as a functional of given density fields n ( r , t ) = ( n 1 ( r , t ), n 2 ( r , t )) T can be expressed by considering fluctuating potential fields ϕ ( r , t ) = ( ϕ 1 ( r , t ), ϕ 2 ( r , t )) T , which are conjugate to n ( r , t ), in addition to an adjusted potential field ϕ dft l ( r , t ) similar to that of the equilibrium DFT. 37,38 Extending the previous result 24,28 to the expression for two-component systems (see Appendix B for details), we havewith the following constraint imposed by the canonical ensemble:where the total number of either anions or cations is equally N . The free-energy functional F [ n , ϕ ] in the exponent of eqn (A3) is defined using the grand potential of the primitive model with an imaginary external field i ϕ ( r ) applied, and can be divided into two parts (see Appendix B for details): F [ n , ϕ ] = F [ n ,0] + Δ F [ n , ϕ ].The free-energy functional F [ n ,0] in the absence of fluctuating potential reduces to the intrinsic Helmholtz free energy, a key thermodynamic quantity in the equilibrium DFT.…”
Section: Appendix a Details On Modifications Of The Pnp Model Present...mentioning
confidence: 87%
See 4 more Smart Citations
“…It has been shown that the constrained free energy as a functional of given density fields n ( r , t ) = ( n 1 ( r , t ), n 2 ( r , t )) T can be expressed by considering fluctuating potential fields ϕ ( r , t ) = ( ϕ 1 ( r , t ), ϕ 2 ( r , t )) T , which are conjugate to n ( r , t ), in addition to an adjusted potential field ϕ dft l ( r , t ) similar to that of the equilibrium DFT. 37,38 Extending the previous result 24,28 to the expression for two-component systems (see Appendix B for details), we havewith the following constraint imposed by the canonical ensemble:where the total number of either anions or cations is equally N . The free-energy functional F [ n , ϕ ] in the exponent of eqn (A3) is defined using the grand potential of the primitive model with an imaginary external field i ϕ ( r ) applied, and can be divided into two parts (see Appendix B for details): F [ n , ϕ ] = F [ n ,0] + Δ F [ n , ϕ ].The free-energy functional F [ n ,0] in the absence of fluctuating potential reduces to the intrinsic Helmholtz free energy, a key thermodynamic quantity in the equilibrium DFT.…”
Section: Appendix a Details On Modifications Of The Pnp Model Present...mentioning
confidence: 87%
“…Details on the constrained free energy of a given density distribution n ( r , t )We consider the overdamped dynamics of ions with the total number N of charged spheres being fixed. Hence, the constrained free-energy functional of a given density distribution n l ( r , t ) ( l = 1,2) is defined for the canonical ensemble using the contour integral over a complex variable w = e μ : 28 In eqn (B1), the Dirac delta functional represents the constraint on the original density distribution . It has been shown for one-component fluid that the constrained free energy functional is expressed by the functional integral over a fluctuating potential field.…”
Section: Appendix a Details On Modifications Of The Pnp Model Present...mentioning
confidence: 99%
See 3 more Smart Citations